Development of Wall-Coated Open Tubular Columns and Their Application to Nano Liquid Chromatography Coupled to Tandem Mass Spectrometry - Natalia G. P. Santos; Deyber A. V. Medina; Fernando M. Lanças (Molecules, 2023)
This work presents a study on the application of wall open tubular column (WCOT) in liquid chromatography coupled with tandem mass spectrometry. Each process step reports the column preparation method in detail, subdivided into column pretreatment, silanization, stationary phase coating, and immobilization. Then, an evaluation of the parameters that can affect the efficiency of these columns was made. Atrazine, clomazone, and metolachlor were used as probes during this step. Factors such as stationary phase composition, length, internal diameter, stationary phase mass employed, and injection volume were investigated. In addition, with the help of Knox and Poppe graphs, the columns’ performance was evaluated to determine the optimal flow rate and the speed-efficiency relationship, respectively. Based on the results, the best configurations for the WCOT column application to the LC system were defined: length—8 m; inner diameter—25 μm; mass of OV-210—2.5% m/v; and, injection volume—100 nL. Finally, the optimized WCOT column developed in this work was coupled with a commercially-packed trapping column in the nano liquid chromatography system (nanoLC). In this configuration, more significant results were obtained regarding separation resolution, with Rs = 5.9 achieved for the most retained pair of analytes (clomazone and metolachlor).